Exploring the effect of brand image on e-WOM through brand value: Evidence from Condor in the Algerian Home Appliance Market - Bouima, Anouar; Redjem, khaled (The International tax journal, 2025)
In the era of digital connectivity, electronic word of mouth (e-WOM) has become a pivotal driver of consumer decision-making and brand success. This study investigates the influence of brand image—conceptualized through cognitive, affective, and behavioral dimensions—on e-WOM, with brand value serving as a mediating construct. Grounded in consumer-based brand equity theory and signaling theory, the study develops a conceptual framework linking how consumers' perceptions of a brand influence their willingness to engage in brand-related online conversations. The research focuses on Condor, a leading Algerian home appliance manufacturer, providing an empirical context from an emerging market. A quantitative approach will be employed using a structured questionnaire distributed to current and potential consumers. Data will be analyzed using Structural Equation Modeling (SEM) to test both direct and indirect effects among the variables. Preliminary expectations suggest that a positive brand image significantly enhances consumers' engagement in e-WOM, and that this relationship is strengthened when brand value—measured through brand awareness, perceived quality, brand associations, and brand loyalty—is high. The study offers practical implications for brand managers aiming to foster online advocacy by enhancing brand perception and value in digitally driven markets.